Development And Utilization of Print Media: Visual Displays And Storyboard - Jannah, Miftahul; Nurjannah, Nurjannah; Sa’duh, Septria; Hasibuan, Restu Permohonan; Bintang, Abdul Rahman; Susanti, Weti (Khalaqa: Journal of Education and Learning, 2024)
Print media remains a powerful tool for communication and learning, especially in education and information dissemination. This research explores the development of print media with a focus on visual design and storyboard use. The method involves analyzing visual elements color, typography, illustration, and the role of storyboards in structuring content flow. Results show that optimal visual design and effective storyboard planning enhance readability, information comprehension, and user experience. Visuals support clearer communication, emotional engagement, faster understanding, and help overcome language barriers. Meanwhile, storyboards enable structured planning, improve production efficiency, foster team collaboration, reduce costs, and allow early concept evaluation. Continuous innovation in print media is essential to keep it relevant to modern society’s needs.